(untitled) (Journal Of Educational and Psychological Researches, 2017)
This study aimed to identify the degree of frustration and guilt among addicts who hurt themselves with drug, and to know the addicts perspective who are in treatment clinics and rehabilitation centers in Palestine, in order to achieve this goal aDeterminationThe study population has been identified , this study population consisted of ’ (82) addict, the researcher used the descriptive analytical method which is appropriate for this study, so the researcher questioned the addicts who are in treatment clinics and rehabilitation centers in Palestine and analyze their responses in light of some of the variables. The study results showed that drug addicts who are in treatment clinics and rehabilitation centers in Palestine suffering from a high degree of frustration in all field that would be related to family , work, friends, Parents , treatment clinics and finally therapeutic supervisor. Also the results showed that drug addicts suffering from a high degree of feeling guilt.